Effect of Sacubitril/Valsartan on Reducing the Risk of Arrhythmia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Ruxin; Ye, Haowen; Ma, Li; Wei, Jinjing; Wang, Ying; Zhang, Xiaofang; Wang, Lihong (Frontiers in Cardiovascular Medicine, 2022)
Background and Objective Relevant data of PARADIGM-HF reveals sacubitril/valsartan (SV) therapy led to a greater reduction in the risks of arrhythmia, and sudden cardiac death than angiotensin converting enzyme inhibitor (ACEI)/angiotensin receptor inhibitor (ARB) therapy in HFrEF, however, inconsistent results were reported in subsequent studies. Here, we conduct a meta-analysis of related randomized controlled trials (RCTs) to evaluate the protective effect of SV on reducing the risk of arrhythmias. Methods and Results RCTs focused on the difference in therapeutic outcomes between SV and ACEI/ARB were searched from PUBMED, EMBASE, ClinicalTrials.gov, and Cochrane Library. The results were extracted from each individual study, expressed as binary risk, 95% confidence interval (CI) and relative risk (RR). Sixteen RCTs including 22, 563 patients met the study criteria. Compared with ACEI/ARB therapy, SV therapy did significantly reduce in the risks of severe arrhythmias among patients with heart failure with reduced ejection fraction (HFrEF) (RR 0.83, 95% CI 0.73–0.95, p = 0.006), ventricular tachycardia (VT) among patients with HFrEF (RR 0.69, 95% CI 0.51–0.92, p = 0.01), cardiac arrest among patients with heart failure (HF) (RR 0.52, 95% CI 0.37–0.73, p = 0.0002), cardiac arrest among patients with HFrEF (RR 0.49, 95% CI 0.32–0.76, p = 0.001), cardiac arrest or ventricular fibrillation (VF) among patients with HF (RR 0.63, 95% CI 0.48–0.83, p = 0.001), and cardiac arrest or VF among patients with HFrEF (RR 0.65, 95% CI 0.47–0.89, p = 0.008), but reduced the risks of arrhythmias (RR 0.87, 95% CI 0.74–1.01, p = 0.07), atrial arrhythmias (RR 0.98, 95% CI 0.83–1.16, p = 0.85), and atrial fibrillation (RR 0.98, 95% CI 0.82–1.17, p = 0.82) among all patients with no significant between-group difference. The merged result was robust after sensitivity analysis, and there was no publication bias. Conclusion Our meta-analysis provides evidence that, compared with ACEI/ARB, SV can additionally reduce the risks of most arrhythmias, just the significant differences are revealed in reducing the risks of VT, severe arrhythmias, and cardiac arrest in patients with HFrEF. Besides, the positive effect of SV on VF according to statistical result of combining VF with cardiac arrest in patients with HFrEF is credibility.